When a Philosopher Refutes Philosophy: The Condition of Ambivalence in Ibn Khaldun’s Refutation of Philosophy - Iqbal, Imam; Farihah, Irzum; Eliawati, Eliawati; Faridah, Euis (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2025)
This article examines Ibn Khaldun’s refutation of philosophy. This refutation is confusing because of his position as a prominent Muslim philosopher. How can a philosopher refute philosophy? In a broader context, Ibn Khaldun’s refutation warrants study because he represents the position of a philosopher-cum-religious figure amid a latent conflict between the rational-philosophical and scriptural-religious perspectives. This article aims to fill the gap in studies regarding Ibn Khaldun’s attitude towards philosophy, which has thus far focused more on his refutation and neglected the relationship between his refutation and his acceptance. To achieve this goal, qualitative research was conducted on Ibn Khaldun’s works along with other writings from journal articles, books, and online literature discussing this topic. Data analysis was carried out using a productive hermeneutic approach to generate a new understanding of his refutation. The research indicates that Ibn Khaldun not only refuted but also accepted philosophy. His stance reveals a persistent condition of ambivalence toward several fundamental philosophical issues. In Ibn Khaldun’s thought, this condition of ambivalence operates as both a discursive and an epistemological strategy, enabling the integration of a rational–philosophical worldview with a scriptural–religious one. Framing his position through this lens of ambivalence, which is advanced in this article as a distinctive analytical perspective, offers a fresh and nuanced understanding of his engagement with philosophy. In the broader context, this perspective of ambivalence serves as a fresh interpretive framework for understanding the refutation of philosophy in the Islamic world, particularly as articulated by a philosopher-cum-religious figure.